A Concept of Constructing a Common Information Space for High Tech Programs Using Information Analytical Systems; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Zakharova A. A. Aleksandra Aleksandrovna (2016, 2016)
Title screen